First record of Dissomphalus Ashmead (Hymenoptera: Bethylidae) from Russia, with description of a new species - Fadeev, Kirill I. (Zootaxa, 2022)
Thе genus Dissomphalus Ashmead is recorded from Russia for the first time. The new species Dissomphalus oksanae sp. nov. is described and illustrated based on males from Krasnodar Territory of Russia. This is the first record of the Western Palaearctic Dissomphalus based on males.